Physicochemical and antioxidant studies on oven-dried, freeze-dried and spray-dried agaro-oligosaccharide powders - Ma’aruf, A. G. (2016)
In this work, oven-dried, freeze-dried and spray-dried agaro-oligosaccharide powders were characterized to investigate their physicochemical and antioxidant properties. Agaro-oligosaccharide powders were shown to exhibit high water solubility index (88.73 – 95.88%), water absorption capacity (0.96 – 2.57 g/g) and oil absorption capacity (0.40 – 0.45 g/g). Agaro-oligosaccharide powders were shown to possess moderate DPPH radical scavenging activity (10.65 – 14.59%), ABTS radical scavenging activity (44 .47 – 65.61%) and ferric reducing antioxidant activity (0.165 – 0.353). Agaro-oligosaccharide powders were further characterized with respect to thermal and pH stability. Agaro-oligosaccharide powders were shown to exhibit high temperature resistance (≤ 100oC) and acid/alkaline resistance.